Factors Affecting Liquidity Risk in Islamic Banking in Pakistan - SHAIKH, SALMAN AHMED (International Journal of Islamic Economics and Governance, 2022)
This study aims to examine the influence of market cost of funds, credit risk, profitability, and size on the funding strategy and liquidity risk in Islamic banking. The analysis utilizes quarterly aggregated time series data on Islamic banking from September 2006 to June 2022. All variables are found to be integrated into order one, indicating they are I(1). The study employs the Vector Error Correction Model (VECM) to investigate the short-run and long-run relationships. The findings indicate that size and credit risk are positively associated with liquidity risk. Furthermore, credit risk demonstrates a long-term co-movement with liquidity risk. Additionally, the results reveal a negative association between profitability and funding strategy, suggesting that higher profitability is associated with a more conservative funding approach. Lastly, the cost of funds exhibits a negative association with funding strategy, implying that lower market cost of funds is linked to a more aggressive funding strategy.‎‎